Factors Related to Sleep Disorders in the Elderly in Tresna Werdha Madago Tentena - Nurmawati S Lataima; Novrin S Pasaju (Universitas Airlangga, 2019)
Background: Sleep disorders are common things often experienced by the elderly. This will affect their quality of life. There are many factors that influence sleep needs in the elderly. The aim of this study was to determine the factors related to sleep disorders in the elderly.Method: This study used a cross-sectional design with accidental sampling. The population in this study was the elderly at Tresna Werdha Madago Tentena. The data retrieval for this research was conducted between June - July 2014. The analysis of the data was done using Chi-Square. The results from the 45 respondents showed that 61.3% had sleep disorders caused by their disease and that 65.6% had sleep disorders caused by an unconducive environment.Result: This result showed that disease and an unconducive environment influenced sleep needs.Conclusion: The recommendation for nurses and staff is to increase their attention span and the environmental comfort by dimming the lights when the patient is going to sleep and reducing noise. This means that the patient's sleep needs are fulfilled.